2012
DOI: 10.1258/hsmr.2011.011015
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for dealing with future shortages in the nursing workforce: a review

Abstract: The well-anticipated and well-documented demographic shift attributed to ageing of the baby boomer generation will place significant demands upon the health-care industry in the future. Significant resources such as the nurse workforce, will be needed to provide health-care services to this cohort. There is a looming shortage of professional and paraprofessional nurses. This paper evaluates strategies that can be utilized to decrease the rate of the nursing shortage, while retaining the current supply of nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…There was high turnover of patients and less number of nurses available. These findings are similar to those identified by Hussain and Buchan [16,17]. Another contributing factor identified in the current study was the pressure exerted on nurses by influential patients to attend to their needs on priority, which further hindered equitable patient care.…”
Section: Discussionsupporting
confidence: 89%
“…There was high turnover of patients and less number of nurses available. These findings are similar to those identified by Hussain and Buchan [16,17]. Another contributing factor identified in the current study was the pressure exerted on nurses by influential patients to attend to their needs on priority, which further hindered equitable patient care.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Gardner identified job stress as the strongest predictor of retention of new graduate nurses 9. Others have found that occupational stressors, burnout, lack of professional latitude, and role problems predicted nurses’ decisions to quit their jobs 1013…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal strategies tailored to the individual appear most successful, but can be resource intensive (Cohen-Mansfield et al, 2015), which is problematic because of health care manpower shortages in a variety of settings (American Health Care Association, 2012; Harrington, Schnelle, McGregor, & Simmons, 2016). To address these shortages, health care leaders recommend technology to facilitate and augment the delivery of efficient, safe care (Hussain, Rivers, Glover, & Fottler, 2012; Institute of Medicine, 2011). Hence, there is an urgent need for efficacious strategies that are tailored to the individual and can exist within various resource-strained environments.…”
mentioning
confidence: 99%